Emergency care providers' perspectives of acute pain assessment and management in the prehospital setting, in the Western Cape, South Africa: A qualitative study. (September 2021) - Lourens, Andrit; Parker, Romy; Hodkinson, Peter
Highlights: Concerns about personal safety and crime influence prehospital practitioners decision-making regarding pain management. The unavailability of medication for non-ALS practitioners to manage pain is a considerable barrier. Organisational factors such as culture, workload, and staff, resource and financial constraints negatively impact prehospital pain care. Emergency department staff lack an understanding of the prehospital environment and scope of practice and criticise prehospital analgesia administration. Abstract: Introduction: A growing body of evidence suggests that pain knowledge and management are poor, perhaps more so in the prehospital setting. The daily challenges that emergency care providers face in dealing with prehospital pain remain unclear. This study aimed to gain a deeper understanding of acute prehospital pain assessment and management in the Western Cape, South Africa. Methods: A series of focus group discussions, using a constructivist paradigm and qualitative content analysis were conducted. Results: The key themes emerging from six focus groups (total 25 emergency care providers) related to the difficulties of assessing pain in this setting, factors affecting clinical reasoning in this (hostile) setting, the realities of prehospital pain care for non-advanced life support practitioners, along with emergency departments' lack of understanding and appreciation of the prehospital environment, and participants' suggestions to improve pain practice. Conclusion: Several barriers and enablers, some novel, to pain assessment and management in the South African prehospital setting were identified. Our findings provide valuable insight and understanding of the challenges related to pain care prehospital providers face, in other similar prehospital settings, but also to the global body of knowledge on prehospital barriers and enablers of pain assessment and management.